LONG-TERM RESULTS OF SURGICAL TREATMENT IN PATIENTS WITH TOXIC GOITER AND SEVERE THYROTOXICOSIS - Viktor O. SHIDLOVSKYI; Oleander V. SHIDLOVSKYI; Michael I. SHEREMET; Igor M. PAVLOVSKYI; Gennady S. KUROCHKIN; Viktoria V. KRAVTSIV; Olga V. SKOCHYLO; Hanna P. HAPLYK; Vitaliy V. MAKSYMYUK; Volodimir V. TARABANCHUK; Nina P. TKACHUK; Antonina A. PIDDUBNA (Archives of the Balkan Medical Union, 2020)
Introduction. The surgical treatment of goiter with severe thyrotoxicosis may lead to an improvement of the general condition of the patient, and amelioration of the clinical manifestations of thyrotoxic cardiomyopathy.